Characterization of anti-HIV-1 neutralizing and binding antibodies in chronic HIV-1 subtype C infection. - Archary, D; Rong, R; Gordon, M; Boliar, S; Madiga, M; Gray, E; Dugast, A; Hermanus, T; Goulder, P; Coovadia, H; Werner, L; Morris, L; et al. (2012)
Neutralizing (nAbs) and high affinity binding antibodies may be critical for an efficacious HIV-1 vaccine. We characterized virus-specific nAbs and binding antibody responses over 21 months in eight HIV-1 subtype C chronically infected individuals with heterogeneous rates of disease progression. Autologous nAb titers of study exit plasma against study entry viruses were significantly higher than contemporaneous responses at study entry (p=0.002) and exit (p=0.01). NAb breadth and potencies against subtype C viruses were significantly higher than for subtype A (p=0.03 and p=0.01) or B viruses (p=0.03; p=0.05) respectively. Gp41-IgG binding affinity was higher than gp120-IgG (p=0.0002). IgG-FcγR1 affinity was significantly higher than FcγRIIIa (p<0.005) at study entry and FcγRIIb (p<0.05) or FcγRIIIa (p<0.005) at study exit. Evolving IgG binding suggests alteration of immune function mediated by binding antibodies. Evolution of nAbs was a potential marker of HIV-1 disease progression.